Repair of Ruptured Sinus of Valsalva Aneurysm: 15 years of Single Center experience - Joshi, Dikshya; Aryal, Marisha; Gurung, Minani; Timala, Rabindra B. (Nepalese Heart Journal, 2022)
Background and Aims: Ruptured sinus of Valsalva aneurysm is an uncommon cardiac anomaly, fatal if not treated in time. This study was designed to retrospectively analyze our 15‐year experience of the surgical repair for ruptured sinus of Valsalva aneurysm and to study the optimal surgical strategy, morbidity, mortality, and long-term surgical outcome. Methods: This study was conducted on 48 (36 Male, and 12 Female) patients of ruptured sinus of Valsalva aneurysm, operated at department of cardiac surgery, Shahid Gangalal National Heart Centre, Nepal, from January 2006 to December 2020 and followed up till March 2021. Follow‐up data were obtained from the outpatient department records and telephone calls. Results: Mean age was 30.17±11.5 (12-63) years. Rupture of the right coronary sinus into the right atrium was the most common anatomic type (52%). Preoperative aortic regurgitation equal to or greater than grade II were seen in 9 patients (19%) and ventricular septal defects in 6 cases (13%). Two patients had preoperative renal failure. One patient had associated aortic root dilatation and underwent modified Bentall’s procedure. Ruptured sinus of Valsalva aneurysm was repaired from single chamber approach in 9 patients, and dual chamber approach in 39. There was a single mortality (2.08%), two patients required permanent pacemaker placement for complete heart block, and two had wound infection. Follow‐up data were available for 36 patients (75%). With the mean follow up of 7.07±3.93 (range, 0.83-15) years, there was no recurrence present. All survivors were in New York Heart Association functional Class I or II. There was one late death, due to non-cardiac cause. Conclusion: Ruptured sinus of Valsalva aneurysm is rare, yet prompt diagnosis and optimal surgical management is crucial in reducing the deleterious effects. Surgical repair of ruptured sinus of Valsalva carries an acceptable low operative risk and can be performed with laudable long-term outcome, with low incidence of recurrence.